PENGARUH LITERASI DIGITAL DAN AKSES MODAL USAHA TERHADAP PENGEMBANGAN UMKM KULINER PADA GENERASI X DAN GENERASI Z DI DENPASAR UTARA - Ida Ayu Ratih RakaSiwi; I Made Adi Suwandana; Anak Agung Istri Agung Ovy Dwijayanthi (Juremi: Jurnal Riset Ekonomi, 2026)
This study aims to examine the influence of digital literacy and access to business capital on the development of MSMEs. The population consists of Generation X and Generation Z entrepreneurs engaged in the culinary sector under the small business category, with business locations in North Denpasar, and a sample of 40 respondents. The data analysis technique applied in this research is multiple linear regression. The findings show that digital literacy has a positive and significant effect on MSME development, and access to business capital also has a positive and significant effect on MSME development; simultaneously, digital literacy and access to business capital significantly affect MSME development. The suggestions provided in this study are that culinary MSME entrepreneurs from Generations X and Z in North Denpasar are expected to improve their ability to reach online markets, which can be achieved by attending seminars or learning about online product marketing, consistently managing existing capital properly to increase income, and enhancing financial literacy while utilizing business capital effectively to achieve the targeted revenue criteria